THE EFFECT OF ADDITION OF POLYSACCHARIDE ON CHARACTERISTICS OF LOW SUGAR CUCUMBER SORBET - Syarifa Ramadhani Nurbaya; Lukman Hudi; Intan Rohma Nurmalasari; Awanda Rizky Amalia (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2021)
Â Â Â The purpose of this study is to determine the effect of adding various types of polysaccharides (CMC, xanthan gum, pectin, agar) and the percentage of polysaccharides (0.5% and 1%) on the characteristics of cucumber sorbet with a low proportion of sugar. This study uses a Randomized Block Design (RBD) with eight treatments and three replications. The results show that the interaction between the types of polysaccharides and the percentage of polysaccharides significantly affects the value of brightness (L) and yellowness (b+) of the sorbet. Based on the results of this study, the best treatment for cucumber sorbet is the cucumber sorbet using 1% xanthan gum. Cucumber sorbet using polysaccharides and a low proportion of sugar can be made as a type of frozen snack that is beneficial to the human body.